Vertebral fractures following stereotactic body radiotherapy for spine metastases. Issue 2 (15th March 2020) - Abbouchie, Hussein; Chao, Michael; Tacey, Mark; Lim Joon, Daryl; Ho, Huong; Guerrieri, Mario; Ng, Michael; Foroudi, Farshad
Summary: Stereotactic body radiotherapy has emerged as one of the preferred treatments for patients with spine metastases, with the potential for long‐term control from lesion irradiation. Post‐treatment vertebral compression fractures are a known complication of this therapy, contributing to worsening pain and reduced quality of life, sometimes requiring surgical intervention. This review explores the current knowledge of post‐radiotherapy fractures, in terms of the rates and associated predictive factors. A search of databases including Medline, Embase and the Cochrane Library was conducted using keywords such as 'vertebral compression fracture', 'stereotactic body radiotherapy' and 'spine metastases'. The search was limited to published studies up to March 2019, reporting clinical outcomes including both the post‐treatment fracture rate and statistical identification of associated risk factors. Rates of post‐treatment fractures ranged from 4 to 39%. A variety of factors were found to increase the risk, including the appearance of lytic vertebral disease, degree of pre‐existing compression, spinal malalignment, increased dose per fraction and a Spinal Instability Neoplastic Score >6. This knowledge can enable clinicians to counsel patients when considering management options for spine metastases, maintaining the balance between local tumour control and the risk of subsequent fracture.